DNA Fingerprinting and Diversity Analysis of BRRI Hybrid Varieties and their Corresponding Parents (Plant Tissue Culture and Biotechnology, 2011)
DNA fingerprinting and genetic diversity of four Bangladesh Rice Research Institute (BRRI) hybrid varieties and their parental lines were carried out. A total of 73 microsatellite markers were tested for screening the genotypes. Among the 73 amplified products, 37% had polymorphic bands showing 81 alleles. The number of alleles per locus ranged from two (RM10) to eight (RM327), where average allele number was 4.333. The Polymorphism Information Contents (PIC) lied between 0.337 (RM10) and 0.852 (RM327). RM327 was the most robust marker providing the highest PIC value (0.852). Pair-wise genetic dissimilarity coefficient interaction showed that BRRI hybrids two was the most genetically distant from each other whereas BRRI hybrids one, three, four and their respective parents were very close. Cluster analysis based on Dices similarity coefficient UPGMA system grouped BRRI hybrid and their parental lines into four major clusters at 0.41 cut off similarity coefficient. Four BRRI hybrid varieties grouped into four distinct clusters along with their component lines indicating their genetic closeness. Key words: Hybrid rice, Diversity analysis, Microsatellite markers, DNA fingerprinting   D. O. I. 10.3329/ptcb.v21i2.10242   Plant Tissue Cult. & Biotech. 21(2): 189-198, 2011 (December)